2017
DOI: 10.1186/s40409-017-0098-7
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and plasma biochemical parameters in a wild population of Naja naja (Linnaeus, 1758) in Sri Lanka

Abstract: BackgroundHematological studies of any animal species comprise an important diagnostic method in veterinary medicine and an essential tool for the conservation of species. In Sri Lanka, this essential technique has been ignored in studies of many species including reptiles. The aim of the present work was to establish a reference range of hematological values and morphological characterization of wild spectacled cobras (Naja naja) in Sri Lanka in order to provide a diagnostic tool in the assessment of health c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…A small drop of blood was taken on a clean dry slide and a uniform film was smeared. Slides were dried in air, fixed in methanol 58,59 and stained in Giemsa and Leishman stain 60,61 . The slides were then washed in running water, dried, dehydrated, cleaned in xylene and mounted.…”
Section: Differential Leucocyte Count (Dlc)mentioning
confidence: 99%
“…A small drop of blood was taken on a clean dry slide and a uniform film was smeared. Slides were dried in air, fixed in methanol 58,59 and stained in Giemsa and Leishman stain 60,61 . The slides were then washed in running water, dried, dehydrated, cleaned in xylene and mounted.…”
Section: Differential Leucocyte Count (Dlc)mentioning
confidence: 99%
“…Several studies already have revealed that composition and clinicopathological effects on vital organs by venom of N. naja have a significant variation in accordance with their originated location [ 16 19 , 34 37 ]. Similar to N. naja in India, the spectacled cobra in Sri Lanka inhabits a wide range of terrestrial habitat, up to an elevation of 1500m [ 38 , 39 ]. Though the distribution of Sri Lankan N. naja is highly variable, Sri Lanka still lacks these systematics studies on Sri Lankan venomous snakes to verify each venom composition and their effect on body according to their geographic diversity and other associated factors.…”
Section: Introductionmentioning
confidence: 99%
“…RBCs of male Naja naja (0.58 AE 0.04 Â 10 6 /μl) are higher than that of the female Naja naja (0.50 AE 0.04 Â 10 6 /μl). PCV of the male (30.11 AE 1.93%) is higher than that of the female (23.41 AE 1.67%), whereas hemoglobin (7.6 AE 0.75 g/dl) is significantly higher in male than in the female Naja naja (3.25 AE 0.74 g/dl), respectively [64]. The difference in the hematological parameters may be due to their nutrition, age, sex, and environment.…”
Section: Effects Of Therapeutic Agents On Erythrocytesmentioning
confidence: 84%